Proceedings of the 26th Annual Conference on Computer Graphics and Interactive Techniques - SIGGRAPH '99 1999
DOI: 10.1145/311535.311553
|View full text |Cite
|
Sign up to set email alerts
|

Reflection space image based rendering

Abstract: High quality, physically accurate rendering at interactive rates has widespread application, but is a daunting task. We attempt to bridge the gap between high-quality offline and interactive rendering by using existing environment mapping hardware in combination with a novel Image Based Rendering (IBR) algorithm. The primary contribution lies in performing IBR in reflection space. This method can be applied to ordinary environment maps, but for more physically accurate rendering, we apply reflection space IBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 28 publications
1
74
0
Order By: Relevance
“…Within the context of rendering surfaces under distant illumination (referred to as environment mapping within computer graphics), many previous authors such as Miller and Hoffman 5 and Cabral et al 6 have qualitatively described reflection as a convolution and have empirically demonstrated that a Lambertian bidirectional reflectance distribution function (BRDF) behaves like a low-pass filter. In computer vision, similar observations have been made by many researchers such as Haddon and Forsyth 7 and Jacobs et al 8 Our main contribution is in formalizing these previous qualitative results by deriving analytic quantitative formulas relating the incoming radiance to the irradiance.…”
Section: Previous Workmentioning
confidence: 99%
“…Within the context of rendering surfaces under distant illumination (referred to as environment mapping within computer graphics), many previous authors such as Miller and Hoffman 5 and Cabral et al 6 have qualitatively described reflection as a convolution and have empirically demonstrated that a Lambertian bidirectional reflectance distribution function (BRDF) behaves like a low-pass filter. In computer vision, similar observations have been made by many researchers such as Haddon and Forsyth 7 and Jacobs et al 8 Our main contribution is in formalizing these previous qualitative results by deriving analytic quantitative formulas relating the incoming radiance to the irradiance.…”
Section: Previous Workmentioning
confidence: 99%
“…[ ] introduced a unified approach to the prefiltering techniques proposed by [Miller and Hoffman 1984], [Heidrich and Seidel 1999], [Kautz and McCool 2000] and [Cabral et al 1999]. Based on this generalized point of view an approximation of the anisotropic BRDF by [Banks 1994] is given.…”
Section: Prefilteringmentioning
confidence: 99%
“…Significant work has been done to approximate these full lighting calculations in real-time using graphics hardware. For example, [1] and [12] described how texture prefiltering and standard texture mapping could be used to interactively render convincing approximations to the illuminated objects in [3], while [13,14,23] use multi-pass rendering methods to simulate arbitrary surface reflectance properties. This paper presents a potential step towards extending these techniques by allowing high-dynamic texture maps to be rendered with hardware acceleration and used for hardware-based lighting calculations.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, when e 1, the low 8 bits of the texture will be amplified and the displayed texture will begin to appear quantized for lack of sufficient low-order bits. This means that restricting e to the range 256 1 In general, the number of textures required to store a texture of bit depth 8n with n 2 is 2n 2. Note that for an 8n-bit texture, the useful exposure range is 256 1 n 1 .…”
Section: I´vµ Clamp´evµmentioning
confidence: 99%
See 1 more Smart Citation